Accounts of bullying on Twitter in relation to dentofacial features and orthodontic treatment. (April 2017) - Chan, A.; Antoun, J. S.; Morgaine, K. C.; Farella, M.
Summary: Social media offers an accessible resource for gaining valuable insights into the social culture of bullying. The purpose of this study was to qualitatively analyse Twitter posts for common themes relating to dentofacial features, braces and bullying. Twitter's database was searched from 2010 to 2014 using keywords relevant to bullying, teeth and orthodontics. Two investigators assessed the Twitter posts, and selected those that conveyed the experiences or opinions of bullying victims. The posts were qualitatively analysed using thematic analysis. Of the 548 posts screened, 321 were included in the final sample. Four primary categories relating to 'dental‐related bullying' were identified: (i) morphological features, (ii) psychological and psychosocial impact, (iii) coping mechanisms and (iv) the role of family. Bullied individuals reported a diverse range of psychological impacts and coping mechanisms. Secondary categories were also identified. Family members, for example, were found to play both a contributory and mediatory role in bullying. In summary, social media can provide new and valuable information about the causal factors and social issues associated with oral health‐related bullying. Importantly, some coping mechanisms may mitigate the negative effects of bullying.